PRIMEIRO REGISTRO DE VESPA-DA-GALHA, Epichrysocaris burwelli (HYMENOPTERA: EULOPHIDAE) EM Corymbia (Eucalyptus) CITRIDORA (Myrtaceae) NO BRASIL - Berti Filho, Evoneo; Costa, Valmir Antonio; LaSalle, John (REVISTA DE AGRICULTURA, 2015)
PRIMEIRO REGISTRO DE VESPA-DA-GALHA, Epichrysocaris burwelli (HYMENOPTERA: EULOPHIDAE) EM Corymbia (Eucalyptus) CITRIDORA (Myrtaceae) NO BRASIL